Participatory Rural Appraisal Dalam Perancangan Kegiatan Budidaya Padi Organik Di Kelurahan Sumpiuh Kabupaten Banyumas - Zulkifli, Lutfi; Rachmah, Malinda Aptika; Ilma, Ajeng Faizah Nijma; Budiyoko, Budiyoko (Lembaga Dongan Dosen, 2025)
The Sumpiuh organic farmers association (Gatos) was a group of farmers committed to cultivating organic rice in Sumpiuh Village, Banyumas Regency. The group was established in 2021 at the initiative of the Sumpiuh Village Head, recognizing the potential market and development opportunities for organic rice in the region. However, the development of organic rice farming in Sumpiuh faced several challenges, including farmers' limited knowledge, the availability of organic fertilizers, and suboptimal product marketing. This community service activity was conducted to identify key issues and design solutions for organic rice cultivation through a participatory approach. The approach utilized was participatory rural appraisal conducted through focus group discussions. Results: The identified issues included land availability, community participation, access to organic farming inputs, and organic rice marketing. The planned activities involved the development of organic rice demonstration plots, organic certification training, and improvements in packaging and digital marketing. The participatory approach, implemented through focus group discussions, successfully enhanced farmer engagement and participation in assessing the challenges they faced and formulating solutions through concrete activities to address these issues.